N-бензгидрил-N'-(трифторацетил)мочевина, проявляющая противосудорожную активность, и способ ее получения - Бакибаев А. А. Абдигали Абдиманапович; Горшкова В. К.; Штрыкова В. В. Виктория Викторовна; Тигнибидина Л. Г.; Саратиков А. С.; Филимонов В. Д. Виктор Дмитриевич; Подтеребина Т. В.; Фоминцева Л. Г.
опубл. 20.04.95, Бюл. № 11